(3TQM GdNRQLjIs - (3CMeO Hf YHO GdQMef Hf eMeO GdfbGhSjs; (3YHO Gddg Hf eMeO GdNRQLj, VjGA GdOjf CHh eMeO,J (B626 (3g` s ((3fhQGdOjf Hf CMeO GdhaGFi GdCRgQj s)
(3ChdgG (B:s
(3hHYO aEf GdTYQ deG cGf TYGQ GdMceI cGf MLI ojQLY Edjg aj JaSjQ eG CTcd ef cJGH Gddg s
(3BNQgG (B:s
(3hGf jaYd Pdc cdg HENhGffG Gddg MSHj hfYe Gdhcjd hGdMeO ddg s
(3GdQGeRI GdNRQLjI GfXQ cTa GdXfhf L (B1 (3U`(B830s
(3L (B2 (3U` (B1135s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdYQhV hGdbhGais